Demographic of orthognathic cases seen in Kulliyyah of Dentistry IIUM - Abu Bakar, Noraini; Amat, Nur Arafiqah; Nasir, Siti Hajjar (IIUM Press, 2023)
Orthognathic treatment is a combination of orthodontics and surgery, aimed to restore functional occlusion and the facial aesthetics. KOD orthognathic team has been established since 2018. There was no published demographic profile of the orthognathic patients referred. This study aimed to enumerate the demographic data and correlations for the orthognathic cases seen in KOD, IIUM from 2018 until December 2020. A total of 28 patients were referred for consultation. One patient was excluded as no referral letter was attached. Data were obtained from patients’ case notes, photos and study models. Data collected were then categorized into patients’ demographic profiles, clinical features, patients’ psychological status and treatment. The demographic pattern and correlations were analysed using SPSS version 25.0. Out of 27 patients, most patients were females (66.7%), Malay (55.6%) and within the age group of 21 to 30 years old (44.4%) and originated from Pahang (88%). Majority of patients presented with Class III skeletal base discrepancy (66.7%), facial asymmetry (76.0%), increased vertical dimension (51.9%), shifted chin point (83.3%), Class III incisal relationship (70.4%), reversed overjet (70.4%), reduced overbite (56.0%) and crossbite (77.7%). Significant relationships were found between skeletal base discrepancy with incisal relationship, overjet, crossbite, canine relationships and right molar relationship. 57.1% agreed to orthognathic surgery, 32.1% opted for orthodontic treatment alone whilst 10.7% refused any treatment. It is hoped that this baseline demographic data may aid in the management and resource planning for this team in the future.